Atypical Wing Venation in Dialictus and Hemihalictus and Its Implications for Subgeneric Classification of Lasioglossum. (10th October 2010) - Gibbs, Jason
Abstract : The subgeneric classification of hundreds of species in Lasioglossum Curtis sensu lato is currently unstable due to differing opinions on the suitability of wing venation characters for differentiating subgenera. The subgenera Dialictus Robertson and Hemihalictus were both originally defined primarily by the forewing having two submarginal cells. I present examples of variation in submarginal cell number in the type species of these two subgenera: L . ( Dialictus ) anomalum (Robertson) and L . ( Hemihalictus ) lustrans (Cockerell). These results suggest that submarginal cell number is insufficient for recognizing subgenera in Lasioglossum . The variability of this character is used to refute the classification proposed by some authors that Chloralictus Robertson, but not Dialictus, be synonymised with Evylaeus Robertson.